Defining dental operative skills curricula: An ADEE consensus paper. (14th September 2020) - Field, James; Dixon, Jonathan; Towers, Ashley; Green, Rachel; Albagami, Hathal; Lambourn, Guy; Mallinson, Julie; Fokkinga, Wietske; Tricio‐Pesce, Jorge; Crnić, Tin; Vital, Sibylle
Abstract: This paper reports on the recent activity of the pan‐European consensus of the ADEE Special Interest Group for Pre‐Clinical Operative Skills. Following the previous recommendations from the group, and in order to support teachers and to harmonise the delivery of skills training across Europe, a more formal curriculum relating to pre‐clinical operative skills needs to be created. This paper reports European consensus surrounding the categorisation (level of importance, and difficulty) of basic operative dental clinical skills within the undergraduate curriculum and provides recommendations relating to session structure and timing of curricular elements for basic operative dental clinical skills teaching.